Origin of gold placers in the Pioneer district, Powell County, Montana - Loen, Jeffrey Scott, author (Colorado State University. Libraries, 1986)
This thesis presents a major reinterpretation of the genesis of gold placers in the Pioneer district, near Deer Lodge, Montana. Previous investigators considered the placers to be the result of glacial deposition and reworking of glacial drift by interglacial streams. Results of this study suggest that the oldest placers, however, occur in two Tertiary conglomerates. Placers are also present in Pleistocene glacial outwash and till, and Holocene alluvium and colluvium. Since 1862 an estimated 300,000 fine ounces of placer gold has been produced from the district, the majority of which came from the Tertiary conglomerates. Conglomerate also served as the principal source for gold in Quaternary age placers. Piedmont slopes in the Pioneer district are underlain by three Tertiary sedimentary sequences separated by unconformities. These are from oldest to youngest: (1)the Cabbage Patch Formation (late Oligocene to early Miocene)--siltstone, mudstone, and volcanic ash deposited in rivers and lakes; (2) the Squaw Gulch beds (Middle Miocene)-siltstone, sandstone, and pebble/cobble conglomerate deposited on alluvial plains by braided streams; and (3) the Pioneer beds (late Miocene or Pliocene (?))--matrix- and clast-supported boulder/cobble conglomerate and siltstone deposited on alluvial fans by mudflows, debris flows, and braided streams. The apparent source of the placer gold is base- and precious-metal veins of late Cretaceous age in the northern Flint Creek Range. Gold was released from the veins during deep weathering under moist, warm climatic conditions in Oligocene and early Miocene time. Middle Miocene mountain uplift and the accompanying arid climate triggered deposition of gold-bearing gravel on mountain-front floodplains. Maximum uplift occurred during late Miocene and Pliocene (?) time when coarse gravels were deposited in alluvial fans. As uplift subsided, braided streams reworked the gold-bearing gravels, forming the richest placers. The present drainage system developed during regional stream incision in middle Pliocene to middle Pleistocene time. Glaciers extended to the margins of the district during four major advances beginning in middle Pleistocene time. Tertiary placers were partly reconcentrated into Pleistocene glacial till and outwash, and Holocene alluvium and colluvium. Electron microprobe analyses and assay results indicate that lode gold from veins in the northern Flint Creek Range has an average fineness range between 800 and 850. Veins in quartzite and slate in the roof zone of the Royal stock contain higher-fineness gold than do veins in granodiorite of the stock. Placer gold from the Pioneer district typically contains cores averaging 830 to 870 fine and silver-depleted rims ranging from 930 to 1000 fine. The depletion of silver in the rims of the gold grains probably resulted from solution of the silver by low-temperature surface waters. Production records indicate an average fineness for the district between 875 and 900. These higher production records reflect the influence of thick silver-depleted rims on many of the placer grains.
Includes map.
Keywords: Geology -- Montana -- Powell County; Placer deposits -- Montana; Gold -- Montana; Gold ores -- Montana -- Powell County; Formations (Geology) -- Montana -- Powell County; Geology, Stratigraphic -- Cenozoic